Frau Ava’s, the first named German female writer’s, poem Jüngstes Gericht ‘The Last Judgement’ and its Lithuanian translation - Burov, Aleksej; Vrubliauskaitė, Ignė (Literatūra, 2019)
The present article offers an overview of several poems written by Frau Ava (1060–1127), a German poetess whose literary works are virtually unknown in Lithuania. Ava, an anchoress in Melk Abbey, is the first named German female writer, who broke ‘the deep silence of German literature’ lasting over a century (Stein 1976, 5). All poems attributed to Frau Ava are of religious character: Johannes ‘John the Baptist’ (446 lines), Leben Jesu ‘Life of Jesus’ (2418 lines), Antichrist (118 lines) and Jüngstes Gericht ‘The Last Judgement’ (406 lines), which make up an impressive biblical epic of 3388 lines. Leben Jesu, Antichrist and Jüngstes Gericht are found in the Vorau Manuscript dating the first half of the 12th century (Codex 276, 115va-125ra), whereas the Görlitz Manuscript (Codex A III. 1. 10), compiled in the 14th century but lost during World War II, contains the poem Johannes as well as the other poems mentioned above, excluding the epilogue of Jüngstes Gericht (lines 393-406). The article presents an overview of Frau Ava’s life and works as well as a Lithuanian translation of her poem Jüngstes Gericht, written in Early Middle High German (Ger. Frümittelhochdeutsch). The translation is based on Maike Glaußnitzer and Kassnadra Sperl’s text, published in 2014.